Paleogeography and shale development characteristics of the Late Permian Longtan Formation in southeastern Sichuan Basin, China. (August 2018) - Lin, Liangbiao; Yu, Yu; Zhai, Changbo; Li, Yehan; Wang, Yanan; Liu, Guangxiang; Guo, Yan; Gao, Jian
Abstract: The Late Permian Longtan Formation is extensively developed within the southeastern Sichuan basin which lies on the western margin of the Yangtze Plate in southwestern China. The stratigraphy and sequence boundaries of the Longtan Formation were interpreted from a combined study of field data, well log data and various data analysis in order to determine the extent and thickness of shale sequences. This interpretation defined the broad sequence stratigraphic framework and separated the Longtan Formation into three 3 rd -order sequences. In addition, the formation was divided into five sedimentary facies using sedimentary, paleontological, geophysical and other data. The facies identified were fluvial, low energy shore, tidal flat, melanged accumulated shelf and platform basin. Three paleogeographic maps were created based on the 3 rd -order sequences: SQ1, SQ2 and SQ3. The study shows that SQ1- SQ3 sedimentary environment of the study area, which extends from the southwest to northeast, was developed followed by fluvial, shore, tide, shallow water melanged accumulation shelf, deep water melanged accumulation shelf and platform basin. The mud shale rock types of the Longtan Formation that were identified are carbonaceous mud shale, silty mudstone and lime mudstone. According to the divided standard of mud shale effective thickness, there are three mud shale assemblages present in the sequences SQ1, SQ2, SQ3, namely, mud shale with sandstone, mud shale with limestone, and mud shale. SQ1 has the thickest mud shale identified on well logs. Mud shale with sandstone was well developed in the southwest of the study area and was interpreted to have been deposited in a shore or tidal flat sedimentary environment. This rock assemblage has a large effective thickness and extensive lateral distribution. In contrast, the assemblage of mud shale with limestone was mainly developed in the northeast of the study area and was interpreted to have formed in a melanged accumulation shelf sedimentary environment. The effective thickness of the mud shale with limestone is small and the distribution is limited. There is developed mud shale in above two type's sedimentary environment, but the distribution is also limited. The Longtan Formation's mud shale reached stage B diagenesis and is principally composed of quartz and clay minerals. The average quartz content is 43.40% and the average clay mineral content, which is mainly composed of illite, mixed illite/smectite, chlorite and kaolinite, is 39.58%. The sedimentary environment has controlled the distribution of minerals within the sequences. The clay mineral content gradually decreases as the sedimentary environment changes from shore-tidal flat in the southwest to deep water melanged accumulation shelf in the northeast. Therefore this comprehensive analysis shows that the southwest of the study area is the key area for shale gas exploration in the Longtan Formation. Highlights: The Longtan Formation was developed fluvial, low energy shore, tidal flat, melanged accumulated shelf and platform basin. The sedimentary environment has controlled the mud shale assemblage and the distribution of minerals within the sequences. The analysis shows that the southwest of the study area is the key area for shale gas exploration in the Longtan Formation.